The indian: from allegory to reality and aesthetics (2004)
In Latín American art. thc topic of the lndian and of lndian aesthetics arouse separately and came together sporadically in the 19th century. México and Perú were the leaders of the movement  at first, with criteria related lo the historical frame implanted by the 19 century academy. In the 20 century there is a political sense that reivindicates the lndian and incorporates him to contemporary society. This process evolved and led to the idea - peculiar to the vanguardist movement- of forging an essencially American art based on indigenous aesthetics.